Sustainable Economic Empowerment for The Creation of Economic Sovereignty in The Karangdoro Village Community - Muhamad Annas; Nurul Inayah (Simfoni Ilmu Cindekia, 2024)
AbstractThis assistance will examine empowerment strategies carried out from a Sustainable Development perspective. This mentoring uses a case study approach with the aim of finding out in depth and comprehensively the empowerment strategies carried out by accompanying lecturers from KH Muhktar Syafa'at Blokagung Banyuwangi University. The data sources used in this assistance are from related parties as well as secondary data sourced from documents and field observations. This assistance found that empowerment strategies include enabling or facilitation strategies with the scope of group discussion activities and the construction of empowerment facilities to generate community motivation, strengthening strategies through activities that focus on increasing community capabilities such as training in forest coffee processing and forest bee cultivation, protection strategies regarding businesses. efforts to form a network of forest coffee farmers and marketing strategies for community non-timber forest products as well as support strategies by participating in technical activities carried out with the abilities possessed such as financial audit and negotiation skills with the Perhutani Forest community. The impact resulting from this empowerment includes three aspects of sustainable development, namely ecological sustainability marked by an increase in the number of fauna found in the Perhutani Forest every year, economic sustainability created by the growth of the community's economic sector other than farming and the growth of community initiatives in preserving the Perhutani Forest which is a characteristic of its birth. social sustainability.